What every mental health professional needs to know about sex - Buehler, Stephanie (Stephanie J.) (New York: Springer publishing, 2022)
"What Every Mental Health Professional Needs to Know About Sex is a straightforward, inclusive, plain language textbook designed to take the provider who knows very little or who might be uncomfortable about sex to a place of knowledge and competence. To accomplish this, Part I: The Courage to Treat Sexual Problems begins in Chapter 1 with a rationale regarding the reasons why all mental health professionals need to be able to address clients' sexual concerns, especially the fact that our current social climate has raised clients' expectations about pleasure. In Chapter 2, the reader will find a model of growth in becoming more comfortable with sexuality-both his or her own and the client's. Psychosexual development and the physiology of sex are covered in Chapter 3, while Chapter 4 covers the recent history of the field of sexology and definitions of sexual health generated by various experts and organizations"--
Sexuality and the Mental Health Profession -- Sexuality and the Self of the Therapist -- Sexual Anatomy and Psychosexual Development -- Evolution of the Field of Sexology and Sexual Health Definitions -- Assessing Sexual Issues -- Women's Sexual Health Problems -- Men's Sexual Health Problems -- Affirming Therapy With Sexual and Gender Minorities -- Relationships and Sex Therapy -- Parents' Questions About Sex -- Sexuality and Mental Health Problems -- Sexual Recovery in Trauma Survivors -- Healing Painful Sex -- Sexuality and Reproduction -- Sexuality and Medical Problems -- Sexually Transmitted Infections -- Sexuality and Aging -- Affirming the Kink Community -- When Sexual Behavior Is Out of Control -- Ethical Management of Sex Therapy Casework -- Sex Therapy : Now and in the Future.
Includes bibliographical references and index.
Keywords: Sexuality -- psychology; Sexual Dysfunctions, Psychological -- therapy; Sexual Behavior -- psychology; Professional-Patient Relations; Psychotherapy